Lower In vivo Myo-Inositol in the Anterior Cingulate Cortex Correlates with Delayed Melatonin Rhythms in Young Persons with Depression - Robillard, Rébecca; Lagopoulos, Jim; Hermens, Daniel F.; Naismith, Sharon L.; Rogers, Naomi L.; White, Django; Carpenter, Joanne S.; Kaur, Manreena; Scott, Elizabeth M.; Hickie, Ian B. (Frontiers in Neuroscience, 2017)
Myo-inositol, a second messenger glucose isomer and glial marker, is potentiated by melatonin. In addition to common abnormalities in melatonin regulation, depressive disorders have been associated with reduced myo-inositol in frontal structures. This study examined associations between myo-inositol in the anterior cingulate cortex and the timing of evening melatonin release. Forty young persons with unipolar depression were recruited from specialised mental health services (20.0 + 3.7 years old). Healthy controls were recruited from the community (21.7 + 2.6 years old). The timing of dim light melatonin onset was estimated using salivary melatonin sampling. Myo-inositol concentrations (MI/CrPCr ratio) in the anterior cingulate cortex were obtained using proton magnetic resonance spectroscopy. After controlling for age, the depression group had significantly lower MI/CrPCr ratios than healthy controls (F(4,75) = 11.4, p = .001). In the depression group, later dim light melatonin onset correlated with lower MI/CrPCr ratio (r = -0.35, p = 0.047). These findings suggest that neurochemical changes in the frontal cortex are associated with circadian disruptions in young persons with depression.